The use of hardened bone cement as an impaction grafting extender for revision hip arthroplasty. (February 2018) - Ruddy, Mark; FitzPatrick, David P.; Stanton, Kenneth T.
Abstract: Impaction bone grafting is a method of restoring bone stock to patients who have suffered significant bone loss due to revision total hip surgery. The procedure requires morsellised cancellous bone (MCB) to be impacted into the site of bone loss in order to stabilise the prosthesis with the aim of long term resorption and reintegration of the impacted bone graft. Due to financial cost and the potential to transmit disease, the use of supplementary material, known as an extender, is frequently used to increase the graft material volume. This study investigates the use of hardened Hydroset (Stryker Corp, MA, USA), an injectable bone cement (IBC), as an extender material and compares the performance of the IBC in different weight percent inclusions to a commercially available bone graft extender (GCP, BoneSave, Stryker Corp, MA, USA). The surgical impaction procedure was standardised and samples were evaluated in terms of graft stiffness and height. It was observed that 30 wt% IBC extended samples had significantly improved graft stiffness ( p = 0.02) and no significant different in height ( p = 0.067) over a 100% MCB control sample. Cyclic loading, representative of gait, found that the IBC subsided similarly to the commercial bone substitute in wt% above 10%. Shear testing of the impacted grafts showed no significant differences between GCP and IBC with impaction forces determining the shear parameters of impacted grafts. The effects of the impaction and cyclical loading procedures on extender particle sizes was assessed via particle size analysis. It was found that the IBC extended samples demonstrated reduced friability, evident in the better retention of particle size as a result of both impaction and gait representative loading compared to that of the GCP samples. This indicates a potential reduction in issues arising from small particle migration to joint surfaces. Scanning electron microscopy of the MCB particles with both GCP and IBC as extenders showed retention of the porous trabecular structure post-testing which is essential for revascularisation and bone growth into the graft. Highlights: The use of injectable bone cement (IBC) as an impaction graft extender is proposed. IBC granules demonstrated reduced friability as compared to surgical standard. IBC content increased initial graft stiffness after impaction. Greater than 10 wt% IBC is required to reduce long term subsidence. Shear properties are dependent on impaction force rather than extender material.